The new Blackwell companion to the city - Bridge, Gary; Watson, Sophie (Malden, MA : Wiley-Blackwell, 2013)
"Drawing together leading scholars from a variety of academic disciplines, this collection reports the leading edge of research and analysis into the contemporary urban condition. With more than half of the world's population living in urban environments, cities are places of huge complexity and diversity and the processes and structures that bind them together reach out across the globe. This volume considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. Whilst considering established themes, such as urban divisions and differences, publics and cultures, politics and planning, the New Blackwell Companion to the City also addresses new debates on subjects like materiality, mobilities, and environment. Incorporating international examples, this book explores the economic, social, cultural, environmental and political issues that flow from and within the modern city"--
"This book considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. The most interdisciplinary collection of its kind. Provides a contemporary update on urban thinking that builds on well established debates in the field Uses the city to explore economic, social, cultural, environmental and political issues more broadly. Includes contributions from non Western perspectives and cities."--
pt.1. City materialities -- Reflections on materialities -- Neoliberal urbanism : cities and the rule of markets -- The liquid city of Megalopolis -- Ups and down in the global city : Londo and New York in the twenty-first century -- Etnography of an Indian city : Ahmedabad -- Landscape and infrastructure in the Late-Modern metropolis -- Objects and the city -- Ecologies of dwelling : maintaining high-rise housing in Singapore -- The urbanization of nature : great promises, impasse, and new beginnings -- One hundred tons to Armageddon : cities combat carbon -- The new military urbanism -- The city's new "trinity" in contemporary Shanghai : a case study of the residencial housing market -- Residence through revolution and reform -- pt.2. City mobilities -- Reflections on mobilities -- "Nothing gained by overcrowding" : the history and politics of urban population control -- Transnationality and the city -- Migrants making technology markets -- Analytic borderlands : economy and culture in the global city -- Nomadic cities -- Mobility and civility : police and the formation of the modern city -- Disease and infection in the city -- Urban choreographies : dance and the politics of space -- Cities on wheels : cars and public space -- pt.3. City affect -- Reflections on affect -- Intensities of feeling : cloverfield, the uncanny, and the always near collapse of the city -- The future of New York's destruction : fantasies, fictions, and premonitions after 9/11 -- Public space? Branding, civility, and the cinema in twenty-first-century China -- The postmetropolis and the mental life : Won Kar-Wai's cinematic Hong Kong -- Imagining Naples : the senses of the city -- City life and the senses -- The politics of urban intersection : materials, affect, bodies -- The city, the psyche, and the visibility of religious -- pt.4. City publics and cultures -- Reflections on publics and cultures -- Reflections on the public realm -- City-zenship in contemporary China : Shanghai, capital of the twenty-first century? -- "Just diversity" in the city of difference -- The emergence of cosmopolitan Soho -- Modernity and Gaslight : Victorian London in the 1950s and 1960s -- The doing undone : vagrancies for the acoustic city -- Sustainable cultural spaces in the global city : cultural clusters in heritage sites, Hong Kong and Singapore -- Spatializing culture : embodied space in the city -- The street politics of Jackie Smith -- Walking and performing "the city" : a Melbourne chronicle -- pt.5. City divisions and differences -- Reflections on division and difference -- The lost urban sociology of Pierre Bourdieu -- Traveling theory : embracing post-neoliberalism -- Race, class, and inequality in the South African city -- Oxford Street, Accra : spatial logics, street life, and the transnational imaginary -- Harlem between ghetto and Renaissance -- Gentrification of the city -- The homosexuality of cities -- Gendering urban space -- Nights in the global city -- pt.6. City politics and planning -- Reflections on politics and planning -- Urban planning in an uncertain world -- The three historic currents of city planning -- Photourbanism : planning the city from above and from below -- Shaping good cities and citizens -- Regional urbanization and the end of the metropolis era -- Invisible architecture : neighborhood governance in China's cities -- Retreat from a totalitarian society : China's urbanism in the making -- Transnational urban political ecology : health and infrastructure in the unbounded city -- Entrepreneurial urbanism, policy tourism, and the making mobile policies -- Making up global urban policies -- Urban governance in Europe : what is governed?
Includes bibliographical references and index.
Keywords: Cities and towns; Ciudades y pueblos; Cities and towns -- Cross-cultural studies; Ciudades y pueblos -- Estudios interculturales